IRF2BP2 3′UTR Polymorphism Increases Coronary Artery Calcification in Men - Vilmundarson, Ragnar O.; Duong, An; Soheili, Fariborz; Chen, Hsiao-Huei; Stewart, Alexandre F. R. (Frontiers in Cardiovascular Medicine, 2021)
Interferon regulatory factor 2 binding protein 2 (IRF2BP2) suppresses the innate inflammatory response of macrophages. A 9-nucleotide deletion (rs3045215) in the 3’ untranslated region (3’-UTR) of human IRF2BP2 mRNA confers risk of coronary artery disease (CAD) in the Ottawa Heart Genomics Study (OHGS). Here, we sought to identify regulatory mechanisms that may contribute to this risk. We tested how lipopolysaccharides (LPS) affects IRF2BP2 expression in human THP-1 macrophages and primary aortic smooth muscle cells (HAoSMC) genotyped for the deletion allele. Both cell types are implicated in coronary atherosclerosis. We also examined how the deletion affects interaction with RNA binding proteins (RBPs) to regulate IRF2BP2 expression. LPS altered allele-specific binding of RBPs in RNA gel shift assays with the THP-1 macrophage protein extracts. The RBP ELAVL1 suppressed the expression of a luciferase reporter carrying the 3’UTR of IRF2BP2 with the deletion allele. Other RBPs AUF1 or KHSRP did not confer such allele specific regulation. Since it is co-inherited with a risk variant for osteoporosis, a condition tied to arterial calcification, we examined the association of the deletion allele with coronary artery calcification in individuals who had undergone computed tomography angiography in the OHGS. In 323 individuals with a minimal burden of atherosclerosis (<30% coronary stenosis) and 138 CAD cases (>50% stenosis), Mendelian randomization revealed that the rs3045215 deletion allele significantly increased coronary artery calcification in men with minimal coronary stenosis. Thus, not only does the rs3045215 deletion allele predict atherosclerosis, but it also predisposes to early-onset calcification in men.